A fluorescent microsphere-based immunochromatographic strip is effective for quantitative fecal blood testing in colorectal cancer screening - Wang, Qingbing; Wang, Jiwu; Xiao, Zeru; Shen, Zhiling; Wang, Yanjun; Zhang, Yong; Pan, Tianyuan; Xiao, Jianan; Sun, Xiyuan (American journal of translational research, 2022)
Colorectal cancer (CRC) represents a major health concern that can be screened for by the fecal immunochemical test (FIT), which detects blood in the stool. CRC detection sensitivity for hemoglobin (Hb) combined with transferrin (Tf) is higher than for hemoglobin alone. We developed a europium fluorescent microsphere-based quantitative lateral flow immunochromatography strip to detect fecal Hb and Tf. Performance was tested using fecal samples from 51 patients with CRC and 122 normal subjects. Test strips were generated using paired mouse anti-human Hb and mouse anti-human Tf monoclonal antibodies and tested using standard Hb and Tf samples. Fluorescence was observed at 365 nm and quantitatively measured using a portable fluorescent strip reader. At cutoff values of 100 ng/mL (10 µg/g feces) and 25 ng/mL (2.5 µg/g feces) for Hb and Tf, respectively, the positive rates for Hb, Tf, and Hb+Tf in normal subjects were 6.56%, 5.74%, and 10.66%, respectively, compared to 88.24%, 64.71%, and 94.12% in patients with CRC. The sensitivity and specificity of the FIT combined detection technique were 87.5% and 89.2%, respectively, and the area under the curve (AUC) was 0.92. The sensitivity, specificity, and AUC for the Tf assay were 63.8%, 68.4%, and 0.759, respectively, and those for Hb testing were 69.7%, 70.2%, and 0.774, respectively. The AUC for Hb+Tf was significantly higher than those for Tf or Hb alone (P < 0.001). Fluorescent microsphere-based immunochromatographic strips sensitively detect fecal Hb and Tf, and sensitivity and specificity are improved for Hb+Tf. This system represents a rapid and portable alternative for on-site early CRC screening.